High extraction ability and selectivity of a tripodal pivalamide derivative for Pt(IV) from hydrochloric acid solutions. Issue 15 (1st November 2016) - Ueda, Yuki; Morisada, Shintaro; Kawakita, Hidetaka; Ohto, Keisuke
ABSTRACT: Secondary pivalamide derivatives of the tripodal compound and the corresponding monopodal analogue have been prepared and these extraction and separation ability for platinum group metals from base metals in chloride media have been studied. The extractability of Pt(IV) with the tripodal extractant was extremely higher than that with the corresponding monopodal one. The extraction equilibrium equation of Pt(II) with the tripodal extractant was determined from slope analysis. To separate Pt(IV) and Pd(II) over base metals, the forward extraction in the metal coexisting system and the stripping from the metal loaded organic phase were carried out.